2019
DOI: 10.1002/ptr.6549
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of isopimarane diterpenoids from Kaempferia galanga

Abstract: Two new isopimarane diterpenes, 1α‐hydroxy‐14α‐methoxyisopimara‐8(9),15‐diene (7) and 1α,14α‐dihydroxyisopimara‐8(9),15‐diene (9) and eight known isopimarane diterpenes including (‐)‐sandaracopimaradiene (1), 6β‐acetoxysandaracopimaradiene‐9α‐ol (2), sandaracopimaradiene‐7β,9α‐diol (3), sandaracopimaradiene‐1α,9α‐diol (4), 6β‐acetoxysandaracopimaradiene‐9α‐ol‐1‐one (5), 6β‐acetoxysandaracopimaradiene‐1α,9α‐diol (6), 6β,14α‐dihydroxyisopimara‐8(9),15‐diene (8), and 6β,14β‐dihydroxyisopimara‐8(9),15‐diene (10) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
0
12
0
1
Order By: Relevance
“…The product of AcKSL3-2 was found to be ent -13- epi -sandaracopimaradiene, making it the first enzyme to be identified to synthesize this diterpene. Other ent -sandaracopimaradiene-like compound derivatives have been isolated from several species including rice 45 , Kaempferia galanga 47 , and Guarea rhophalocarpa 48 ; however, it has not reported previously in Aconitum . On the other hand, beside ent -13- epi -sandaracopimaradiene, it also produced ent -kaurene and another unknown diterpene in the engineered E. coli .…”
Section: Discussionmentioning
confidence: 95%
“…The product of AcKSL3-2 was found to be ent -13- epi -sandaracopimaradiene, making it the first enzyme to be identified to synthesize this diterpene. Other ent -sandaracopimaradiene-like compound derivatives have been isolated from several species including rice 45 , Kaempferia galanga 47 , and Guarea rhophalocarpa 48 ; however, it has not reported previously in Aconitum . On the other hand, beside ent -13- epi -sandaracopimaradiene, it also produced ent -kaurene and another unknown diterpene in the engineered E. coli .…”
Section: Discussionmentioning
confidence: 95%
“…For further process to identify the bioactive compound of succinum, we confirmed that EtOAc PSF was most similar to the PSE effect among the three fractions ( Supplementary Figures S2A,B ). In recent, isopimarane diterpenes showing anti-inflammation properties have been proposed as a bioactive compound of succinum, and it ameliorated cognitive impairment via inhibiting hippocampal apoptosis ( Tungcharoen et al, 2020 ; Wei et al, 2022 ). As mentioned above, we speculate that terpenes-based compounds may involve with the anti-neuroinflammatory and antidepressant-like effects.…”
Section: Discussionmentioning
confidence: 99%
“…EIMS analysis afforded an M + ion at m/z 272.2. Compound 9 was identified as isopimara-8( 14),15-diene based on the comparison of its 1 H NMR data (Table S5) and 13 C NMR data (Table S6) with authentic data published before 41 . The absolute configuration assignments of 2-7 were also benefitted by the structure of syn-CPP, whose absolute configurations have already been set from the catalysis of the class II DTS OsCPS4.…”
Section: Methodsmentioning
confidence: 99%